Yield Regulation in the Madras Forests - Achaya, T.; Bhadran, C. A. R. (Indian Forester, 1961)
The Madras forests include evergreen, moist deciduous, dry miscellaneous and dry sandal types besides the temperate region plantations of Eucalyptus and wattle. Bamboos have also received special attention. The progress of working plan prescriptions is traced in respect of each of these types, particularly with regard to the determination of growth, rate outturn, rotation and yield. The variations in prescriptions from one locality to another are also indicated. The collection of growth and stand data, mainly to provide basis for an over-all check or for control of removals under an area yield, has been characteristic of the efforts to ensure a sustained yield. The peculiar features of management of sandal forests and of bamboo areas are brought out. The adverse effects of World War II on yield regulation in the Madras State are listed. The conclusion is drawn that further work is necessary to regulate yield at least by equiproductive or 'reduced' areas.